Síntese de Antenas com Refletor Principal Esférico para Geração de Feixe ColimadoDOI: 10.14209/jcis.1993.4 - R. Bergmann, J.; C. W. A. da Costa, J. (Journal of Communication and Information Systems, 2015)
The design of dual-reflector antennas with a spherical main reflector for small stations is considered. An analysis of the field polarization throughout the system shows that is possible to adjust the reflector to obtain very low cross-polarization. The use of an elliptical main reflector projection is explored in order to enhance efficiency and lower side-lobe levels.